Aquinas, Descartes and the Unity of Substantial Form - Thomas, James (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2017)
The Thomistic doctrine of the unity of substantial form accounts for the Cartesian mind’s close unity with body, but for their independence Paul Hoffman advised the pluralist reading of the composite attributable to William of Ockham and Duns Scotus. Principally to link Cartesian thought to a more extensive ethical tradition, I suggest that the Thomistic doctrine could be developed to respond to Marleen Rozemond’s objections to a scholastic reading if the substantial form is taken to be the argument to incline the conatus or appetite of existence.